2014
DOI: 10.12693/aphyspola.126.811
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Contribution in Thermodynamics and Transport Properties of Ultrathin Ceramic Films

Abstract: The dispersion law, density states of phonons, thermodynamics properties and thermal conductivity was analyzed in this paper. It has been shown that at low temperatures, thermal conductivity of thin lm is considerably lower that of bulk-structure. It turned out that phonons in thin lm require activation energy for exciting. This leads to extremely low specic heat and specic conductivity at low temperatures. Consequences of quoted facts were discussed in detail and their inuence on kinetic and thermodynamic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Based on the formed models of ultrathin films, super-lattices, quantum wires and dots, as well as monitored microscopic and macroscopic features of such crystalline systems, we showed an extremely large influence of the decrease of spatial dimensions and boundary conditions to the change of physically relevant (optics, thermodynamics and electro transporting) characteristics of crystal substances [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Critical temperatures up to 100 K are explained here: although the effects of electron-phonon interaction (as in BSC-theory) are still not calculated.…”
Section: Research Reasons Achieved Resultsmentioning
confidence: 99%
“…Based on the formed models of ultrathin films, super-lattices, quantum wires and dots, as well as monitored microscopic and macroscopic features of such crystalline systems, we showed an extremely large influence of the decrease of spatial dimensions and boundary conditions to the change of physically relevant (optics, thermodynamics and electro transporting) characteristics of crystal substances [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Critical temperatures up to 100 K are explained here: although the effects of electron-phonon interaction (as in BSC-theory) are still not calculated.…”
Section: Research Reasons Achieved Resultsmentioning
confidence: 99%
“…But it is also established that poor conductors (under normal conditions) are at the same time the best superconductors, and vice versa [4,[15][16][17][18][21][22][23]. Against this background, it can be concluded that in the spatially very limited structures the best superconducting properties can be expected, or that restriction of the spatial dimensions of the structure plays a major role in improving superconducting properties of material.…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of phonon contribution in thermodynamic properties of low-dimensional structures (ultra-thin film and superlattice) was the subject of our previous investigations and has been referred [4,10,11,[15][16][17][18][19][20] in the past period. Here, we will use some of these results in order to compare them with the results obtained in this paper for ultra-narrow wires.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…[25][26][27][28]. After a substitution of found commutators and the application of the partial configuration Fourier transformation (due to the disturbance of translational symmetry of considered system, this transformation is applied to coordinates x, y and z but not to coordinate l, where the translational symmetry is disturbed), one obtains the system of non-homogeneous algebraic-differential equations for Green's functions: (i) Order N z + 1 for film:…”
Section: -4mentioning
confidence: 99%
“…The poles of Green's functions, determining the dispersion laws of phonons, are found by setting the value of determinant D to zero. Expanding the determinant through numerical calculations only, [26][27][28] we provide the adequate number of values for , i.e. for frequencies ω k .…”
Section: -4mentioning
confidence: 99%